Efektivitas Pelaksanaan E-Complaint (Studi Kasus pada Pusat Informasi, Dokumentasi, dan Keluhan Universitas Brawijaya) - Kurniawan, Fajar Andy (Jurnal Ilmiah Administrasi Publik, 2018)
The main purpose of this research is to analyze the effectiveness of e-complaint implementation, and to find out the constraints faced in the implementation. The theory used is the theory of public service. This research was designed with qualitative descriptive method, data collected through interview, documentation and observation methods. The results of this study indicate that: first, the implementation of e-complaint UB as a whole has been running well, both in terms of input, output and productivity. Although in terms of process is still not optimal. Second, there are some obstacles faced in the implementation of ecomplaint. Which is divided into two, internal and external. Internal obstacles include: human resources, internet network, and e-complaint application maintenance costs. External constraints include: the lack of feedback from service users and the mindset of service provider and service user who do not consider the importance of e-complaint.